Are the Obese Patients and Patients with Severe Malnutrition at Increased Risk of Severe Coronavirus Disease 2019 during Hospital Admission? - Markovska, Zorica; Mijakoski, Dragan; Kuzmanova, Katerina; Meshkova, Iskra; Tusheva, Ivana; Stoleski, Sasho (Scientific Foundation SPIROSKI, 2020)
BACKGROUND: Recently, authorities highlighted the need for nutritional management of individuals with severe acute respiratory syndrome coronavirus 2 infection. AIM: The aim of the study was to evaluate the use of body mass index (BMI) and nutrition risk index (NRI) on hospital admission for detecting patients at risk for malnutrition and obesity and their association with patients’ outcomes (disease type, length of hospital and home stay, and inflammatory markers). METHODS: The study of 100 patients with confirmed diagnosis Coronavirus Disease-19 (COVID-19). Assessment of patients took place at City General Hospital 8th September, Skopje, transformed into main COVID-19 Center during pandemic. Primary outcomes were NRI and BMI scores, while secondary ones: length of home and hospital stay, number of symptoms, presence of co-morbidities, type of disease, serum albumin, and C-reactive protein (CRP). RESULTS: Patients were classified according to BMI and NRI scores. Increased BMI and NRI were associated with a severe type of disease. Most of the patients with severe disease were: obese (83.3%) and patients with risk for malnutrition (53.3%). Obese patients had a longer length of home stay and higher CRP levels, but the level of albumin was lower in a group with a risk for malnutrition. CONCLUSION: Future studies are needed to identify and quantify specific screening tool for nutrition deficiency in patients with COVID-19 infection.
Keywords: Nutritional assessment; Obesity; Malnutrition; Risk; Coronavirus disease-19